Genomic Characterization of Antibiotic-Resistant Campylobacterales Isolated from Chilean Poultry Meat - Macarena Concha-Toloza; Mónica Lopez-Cantillo; Jose Arturo Molina-Mora; Luis Collado (Antibiotics, 2023)
Due to the lack of knowledge about Campylobacterales in the Chilean poultry industry, the objective of this research was to know the prevalence, resistance, and genotypes of Campylobacter, Arcobacter and Helicobacter in 382 samples of chicken meat purchased in Valdivia, Chile. The samples were analyzed using three isolation protocols. Resistance to four antibiotics was evaluated by phenotypic methods. Genomic analyses were performed on selected resistant strains to detect resistance determinants and their genotypes. A total of 59.2% of the samples were positive. Arcobacter butzleri (37.4%) was the most prevalent species, followed by Campylobacter jejuni (19.6%), C. coli (11.3%), A. cryaerophilus (3.7%) and A. skirrowii (1.3%). Helicobacter pullorum (14%) was detected by PCR in a subset of samples. Campylobacter jejuni was resistant to ciprofloxacin (37.3%) and tetracycline (20%), while C. coli and A. butzleri were resistant to ciprofloxacin (55.8% and 2.8%), erythromycin (16.3% and 0.7%) and tetracycline (4.7% and 2.8%), respectively. Molecular determinants were consistent with phenotypic resistance. The genotypes of C. jejuni (CC-21, CC-48, CC-49, CC-257, CC-353, CC-443, CC-446 and CC-658) and C. coli (CC-828) coincided with genotypes of Chilean clinical strains. These findings suggest that besides C. jejuni and C. coli, chicken meat could play a role in the transmission of other pathogenic and antibiotic-resistant Campylobacterales.